Summary and Conclusion [In Fostering transformation and growth in Niger’s agricultural sector] - Wouterse, Fleur Stephanie (Wageningen Academic Publishers, 2018)
For Niger, the development of agriculture is essential to strategies to raise incomes and eradicate poverty in a sustainable manner, that is without further depleting its natural resource base. Africa is increasingly emphasising the role of innovation in development. The Science, Technology and Innovation Strategy for Africa 2024, for example, takes into consideration the social, economic, and technological progress Africa has made over the last decade. Innovation for sustainable agricultural growth forms an important part of this ambition. Traditional approaches to agricultural development have emphasised food security and have been rather technology focused – helping farmers to grow enough to feed themselves and their families, and perhaps a surplus to sell. However, reducing rural poverty across the board requires more than a green revolution. More recently, concern with markets has become prominent. Even subsistence farmers need cash, goes the reasoning; they need to be able to grow things they can sell. And if they have a market for their produce, they have an incentive to grow more to earn more. This ushers in a virtuous cycle of higher yields and production, greater incomes, higher living standards, and more investment in production. The agricultural value chain perspective provides a reference point for improvements in supporting services and the business environment and can contribute to pro-poor initiatives and better linking of smallholders to markets. In summary, this volume has shed light on several interesting innovations that could contribute to enhancing agricultural productivity. Particularly interesting is the emphasis on the grassroots nature of some of these innovations. At the same time, the chapters also highlight changes to the institutional environmental that could further enhance Niger’s sustainable agricultural transformation.